Disparities in Fertility-Sparing Treatment and Use of Assisted Reproductive Technology After a Diagnosis of Cervical, Ovarian, or Endometrial Cancer. Issue 2 (4th February 2023) - Jorgensen, Kirsten; Meernik, Clare; Wu, Chi-Fang; Murphy, Caitlin C.; Baker, Valerie L.; Jarmon, Peiton; Brady, Paula C.; Nitecki, Roni; Nichols, Hazel B.; Rauh-Hain, Jose Alejandro
Abstract : Disparities exist in fertility-sparing treatment and the use of assisted reproductive technology among patients with gynecologic malignancies. Abstract : OBJECTIVE: To assess the presence of sociodemographic and clinical disparities in fertility-sparing treatment and assisted reproductive technology (ART) use among patients with a history of cervical, endometrial, or ovarian cancer. METHODS: We conducted a population-based cohort study of patients aged 18–45 years who were diagnosed with cervical cancer (stage IA, IB), endometrial cancer (grade 1, stage IA, IB), or ovarian cancer (stage IA, IC) between January 1, 2000, and December 31, 2015, using linked data from the CCR (California Cancer Registry), the California Office of Statewide Health Planning and Development, and the Society for Assisted Reproductive Technology. The primary outcome was receipt of fertility-sparing treatment, defined as surgical or medical treatment to preserve the uterus and at least one ovary. The secondary outcome was fertility preservation, defined as ART use after cancer diagnosis. Multivariable logistic regression analysis was used to estimate odds ratios and 95% CIs for the association between fertility-sparing treatment and exposures of interest: age at diagnosis, race and ethnicity, health insurance, socioeconomic status, rurality, and parity. RESULTS: We identified 7, 736 patients who were diagnosed with cervical, endometrial, or ovarian cancer with eligible histology. There were 850 (18.8%) fertility-sparing procedures among 4, 521 cases of cervical cancer, 108 (7.2%) among 1, 504 cases of endometrial cancer, and 741 (43.3%) among 1, 711 cases of ovarian cancer. Analyses demonstrated nonuniform patterns of sociodemographic disparities by cancer type for fertility-sparing treatment, and ART. Fertility-sparing treatment was more likely among young patients, overall, and of those in racial and ethnic minority groups among survivors of cervical and ovarian cancer. Use of ART was low (n=52) and was associated with a non-Hispanic White race and ethnicity designation, being of younger age (18–35 years), and having private insurance. CONCLUSION: This study demonstrates that clinical and sociodemographic disparities exist in the receipt of fertility-sparing treatment and ART use among patients with a history of cervical, endometrial, or ovarian cancer.